Digital Storytelling as a Pedagogical Strategy and Literary Analysis: A Systematic Literature Review - Aldian Yusup (Mandalika Institute, 2026)
The development of digital technology has brought significant changes in the world of education, including in language learning and literary studies. One of the innovations that stands out is digital storytelling, which is the practice of storytelling by utilizing digital media to present a more interactive and contextual narrative. This research departs from the urgency of the need for English learning methods that are adaptive to the digital generation as well as relevant to the phenomenon of fragmented self in contemporary literature. The purpose of the research is to systematically review the literature related to digital storytelling and fragmented self with a focus on pedagogical contributions and theoretical implications in literary studies. The method used is Systematic Literature Review (SLR) with the PRISMA 2020 flow. The selection process was carried out through the Scopus database with the keywords